Lysine Methyltransferase Inhibitors Impair H4K20me2 and 53BP1 Foci in Response to DNA Damage in Sarcomas, a Synthetic Lethality Strategy - Campillo-Marcos, Ignacio; Monte-Serrano, Eva; Navarro-Carrasco, Elena; García-González, Raúl; Lazo, Pedro A. (Frontiers in Cell and Developmental Biology, 2021)
Background: Chromatin is dynamically remodeled to adapt to all DNA-related pro-cesses, including DNA damage responses (DDR). This adaptation requires DNA and histone epigenetic modifications, which are mediated by several types of enzymes; among them are lysine methyltransferases (KMTs). Methods: KMT inhibitors, chaetocin and tazemetostat (TZM), were used to study their role in the DDR induced by ionizing radiation or doxorubicin in two human sarcoma cells lines. The effect of these KMT inhibitors was tested by the analysis of chromatin epigenetic modifications, H4K16ac and H4K20me2. DDR was monitored by the for-mation of γH2AX, MDC1, NBS1 and 53BP1 foci, and the induction of apoptosis. Results: Chaetocin and tazemetostat treatments caused a significant increase of H4K16 acetylation, associated with chromatin relaxation, and increased DNA damage, detected by the labeling of free DNA-ends. These inhibitors significantly reduced H4K20 di-methylation levels in response to DNA damage and impaired the recruitment of 53BP1, but not of MDC1 and NBS1, at DNA damaged sites. This modification of epigenetic marks prevents DNA repair by the NHEJ pathway and leads to cell death. Conclusion: KMT inhibitors can function as sensitizers to DNA damage-based thera-pies and be used in novel synthetic lethality strategies for sarcoma treatment.